The Influence of Employee Voice Mechanism and Organizational Climate on Employee Engagement and Innovation Culture in the Karawang Manufacturing Industry - Rosid, Muhammad Abdul; Muhtadin, Imam; Rahayu, Estri Purwani; Darojat, Ilma; Isrok, Isrok (Westscience Press, 2026)
This study investigates the influence of employee voice mechanisms and organizational climate on employee engagement and innovation culture in the manufacturing industry in Karawang, Indonesia. Employing a quantitative research design, data were collected from 120 employees using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to examine both the measurement and structural models. The results indicate that employee voice mechanisms and organizational climate have significant positive effects on employee engagement. Organizational climate demonstrates a stronger influence, highlighting the importance of a supportive and open work environment in enhancing employee involvement. Furthermore, both employee voice mechanisms and organizational climate significantly affect innovation culture. Employee engagement is also found to have a significant positive impact on innovation culture and plays a partial mediating role in the relationship between the independent variables and innovation culture. These findings suggest that organizations in the manufacturing sector should prioritize the development of effective communication channels and foster a positive organizational climate to enhance employee engagement and promote innovation. This study contributes to the literature by integrating key organizational behavior variables into a comprehensive model and provides practical implications for improving organizational competitiveness through human resource strategies.